2018
DOI: 10.1016/j.chom.2017.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Fiber-Mediated Nourishment of Gut Microbiota Protects against Diet-Induced Obesity by Restoring IL-22-Mediated Colonic Health

Abstract: Dietary supplementation with fermentable fiber suppresses adiposity and the associated parameters of metabolic syndrome. Microbiota-generated fiber-derived short-chain fatty acids (SCFAs) and free fatty acid receptors including GPR43 are thought to mediate these effects. We find that while fermentable (inulin), but not insoluble (cellulose), fiber markedly protected mice against high-fat diet (HFD)-induced metabolic syndrome, the effect was not significantly impaired by either inhibiting SCFA production or gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
425
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 434 publications
(458 citation statements)
references
References 41 publications
30
425
0
3
Order By: Relevance
“…Indigestible carbohydrates including inulin, galacto‐oligosaccharide, xylooligosaccharide, and soybean oligosaccharides, have been found to suppress obesity by the alteration of the gut microbiome and microbial metabolites . Similarly, we also found that MOS increased the SCFAs production and balanced the microbiome in WD‐fed mice.…”
Section: Discussionsupporting
confidence: 66%
“…Indigestible carbohydrates including inulin, galacto‐oligosaccharide, xylooligosaccharide, and soybean oligosaccharides, have been found to suppress obesity by the alteration of the gut microbiome and microbial metabolites . Similarly, we also found that MOS increased the SCFAs production and balanced the microbiome in WD‐fed mice.…”
Section: Discussionsupporting
confidence: 66%
“…81 In mouse models of obesity, fiber supplementation prevented inflammation and metabolic syndrome by restoring IL-22 production within the colon. 82 Diets high in fiber tend to have higher microbial richness and diversity with an abundance in such genera as Prevotella and Treponema. 83 These shifts have been linked to a decreases in inflammatory signaling, protection against obesity, and possibly decreases in the presence of colorectal cancer.…”
Section: Environmental Factorsmentioning
confidence: 99%
“…Regarding prebiotics, in mice, dietary supplementation with inulin, a fermentable fiber that results in SCFA generation, but not cellulose, an insoluble fiber that is not readily fermented, provides protection from the metabolic effects of high fat diets, including glucose tolerance and insulin resistance (132). There is some evidence that inulin might also be beneficial in asthmatics.…”
Section: Mechanistic Basis For the Role Of Obesity In Severe Asthmamentioning
confidence: 99%